Exploring Relationships Between Genito-Pelvic Pain/Penetration Disorder, Sex Guilt, and Religiosity Among College Women in the U.S. Issue 4 (20th March 2021) - Azim, Katharina A.; Happel-Parkins, Alison; Moses, Amy; Haardoerfer, Regine
ABSTRACT: INTRODUCTION: Despite a growing body of research on psychosocial factors in Genito-Pelvic Pain/Penetration Disorder (GPPPD) during sexual intercourse, there are few studies examining adolescent and young adult women's experiences with painful sex and the effects of religiosity, sexual education, and sex guilt. Aim: The purpose of the study was to examine the occurrence of GPPPD among sexually active female college students, including psychosocial factors of religiosity and religious practice, sexual education, sex guilt, and sexual distress. Methods: Data were collected from 974 college women from a university in the Northeastern U.S. We limited our sample to sexually active women ( n = 593, 60.9%; mean age: 18.96) who responded to the questionnaire item, "In general, do you feel pain with sexual intercourse?" Participants completed the Female Sexual Function Index (FSFI), Female Sexual Distress Scale (FSDS), Revised Mosher Sex Guilt Scale, Abbreviated Santa Clara Strength of Religious Faith Questionnaire, 10-item Gender Role Beliefs Scale, and measures on sexual wellness and practice and sexual education experiences. Data were analyzed using standard bivariate and regression analyses as well as path analysis. Main Outcome Measures: Women were asked, "In general, do you feel pain with sexual intercourse?" and categorized into one of three pain groups: occasional (10%–25% of the time), frequent (50% or more), and no pain (less than 10%). RESULTS: GPPPD with sex was prevalent among young college women, with 113 (19.1%) reporting frequent pain and 143 (24.1%) occasional pain (control n = 337, 56.8%). Numerous statistically significant factors were identified, including frequency of sex, ability to orgasm, sensations during intercourse, presence of a steady sexual partner, expectations of painful sex, sex guilt, and sexual distress. Sex guilt acted as full mediator between religiosity and painful sex. Implications: Healthcare providers should proactively initiate conversations with young female patients about painful intercourse to identify issues and normalize language on pain with sex. Educators are urged to teach evidence-based information on pain-free and guilt-free sexual experiences inside and outside religious contexts. CONCLUSION: Painful sex affects adolescent and young adult women at a similar rate as non-college adult women and while religiosity does not directly impact young women's GPPPD, religiosity does lead to painful sex if it causes sex guilt. Further research is needed into the mechanisms of religion-based sexual shaming and among religiously conservative women who practice abstinence until marriage.